NiCuZn ferrite material as well as preparation method and application thereof
By adjusting the main components and introducing side components, the composition and sintering process of NiCuZn ferrite materials are optimized, and the problem of excessive change rate of inductance in traditional materials in high-temperature load tests is solved, and the demand for high-reliability electronic device materials is achieved.
Patent Information
- Application Number
- CN202411973694.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-28
AI Technical Summary
The inductance rate of traditional NiCuZn ferrite materials is too large in high temperature load tests, which cannot meet the material needs in the field of high-reliability electronic devices.
By adjusting the content of Fe2O3, NiO, ZnO, CuO, and Co2O3, and introducing Bi2O3, Y2O3, and In2O3 as sub-components, a low-temperature sintering process is adopted to control the sintering temperature and time, and optimizing the grain structure and grain boundary distribution.
The high reliability of NiCuZn ferrite material is achieved, the rate of change in inductance in high-temperature load tests is reduced, and the material needs in the field of high-reliability electronic devices are met.
Smart Images

Figure CN119724808A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of soft ferrites, and in particular to a NiCuZn ferrite material and a preparation method and application thereof. Background Art
[0002] With the development of electronic equipment that is thin, light, short, integrated, intelligent and multifunctional, higher requirements are put forward for the miniaturization of electronic components. Laminated chip inductors, magnetic beads and other chip devices use advanced thick film multilayer printing technology and laminated production process to achieve ultra-small surface mounting, breaking through the limitation that traditional winding inductors cannot be miniaturized, and adapting to the development trend of miniaturization of electronic components. Low-temperature sintered NiCuZn ferrite material is the key basic material for laminated chip devices to achieve practical application, so the performance of low-temperature sintered NiCuZn ferrite material directly determines the performance of laminated chip devices. Laminated chip inductors, magnetic beads, etc. are made by casting ferrite materials into sheets, alternately printing and laminating with conductor Ag paste, and sintering at about 900℃. They can match and co-fire with Ag paste, and have good electromagnetic properties. They are widely used in the field of laminated chip inductors, magnetic beads and other chip devices, and play an important role in the fields of inductance, filtering, and anti-electromagnetic interference. Its use prospects and promotion space are very large.
[0003] However, as the types of electronic devices become more and more diverse, and the number of electronic products equipped with them increases, the market's requirements for these electronic products are also getting higher and higher, requiring stable product performance and high reliability; requiring that the electromagnetic performance of the product should not have large deviations during use, which would affect the quality of the product. As the requirements for products increase, higher requirements are also placed on ferrite materials. Traditional ferrite materials have problems such as excessive welding change rate of inductor products and excessive change rate of inductance in high-temperature load tests. They are no longer suitable for high-reliability application fields, resulting in their inability to be promoted in some fields that require high-stability devices.
[0004] Therefore, there is an urgent need to prepare high-reliability NiCuZn ferrite materials to meet the material application in the field of high-reliability electronic devices.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The object of the present invention is to provide a NiCuZn ferrite material and a preparation method and application thereof, aiming to provide a NiCuZn ferrite material with high reliability and reduce the inductance change in a high temperature load test.
[0007] The present invention is achieved in that:
[0008] In a first aspect, the present invention provides a NiCuZn ferrite material, comprising a main component and a subsidiary component;
[0009] Among them, according to the amount of the total substance of the main components, the main components include: Fe 2 O 3 47.5~48.7mol%, NiO18.0~18.6mol%, ZnO23.3~24.1mol%, CuO 9.50~9.90mol% and Co 2 O 3 0.48~0.50mol%;
[0010] Relative to the total weight of the main component, the auxiliary components include: Bi 2 O 3 1.40~1.60wt%, Y 2 O 3 0.08~0.15wt% and In 2 O 3 0.05~0.10wt%.
[0011] In an optional embodiment, relative to the total weight of the main component, the auxiliary components include: Bi 2 O 3 1.48~1.52wt%, Y 2 O 3 0.09~0.11wt% and In 2 O 3 0.05~0.07wt%.
[0012] In a second aspect, the present invention provides a method for preparing the NiCuZn ferrite material of the aforementioned embodiment, comprising: preparing the NiCuZn ferrite material satisfying the component composition requirements by mixing the ingredients according to the composition of the main component and the auxiliary component.
[0013] In an optional embodiment, the method comprises: firstly batching, mixing and pre-firing the main components according to the composition of the main components to obtain a main component pre-firing material;
[0014] The main component pre-sintered material and the auxiliary component are mixed and crushed, and then ultrasonically activated to obtain an activated material;
[0015] Granulating and pressing the activated material to obtain a blank;
[0016] The green part is sintered.
[0017] In an optional embodiment, after the ingredients are prepared according to the composition of the main component, the raw materials are mixed by ball milling, and the ball material water mass ratio is controlled to be (4.8-5.1): (0.9-1.0): (1.1-1.2), and the mixing time is 50min-60min;
[0018] And / or, during the preparation of the main component pre-burned material, the pre-burning temperature is controlled to be 810° C. to 830° C., and the insulation time is 2.0 h to 2.2 h.
[0019] In an optional embodiment, the main component pre-sintered material and the auxiliary components are pulverized by wet pulverization, the pulverization time is 120min to 130min, and the median particle size of the slurry after pulverization is 0.95μm-1.10μm;
[0020] And / or, the ultrasonic activation treatment includes: subjecting the pulverized slurry to ultrasonic pulverization, so that the D10, D50, and D90 particle sizes of the particles in the slurry are all <1.0 μm, and the slurry temperature is controlled at 80° C.-85° C. during the pulverization process.
[0021] In an optional embodiment, the granulation process includes: mixing the activated material with a polyvinyl alcohol solution and centrifuging the granules; the mass fraction of the polyvinyl alcohol solution is 7%-9%, and the mass ratio of the solid mass in the activated material to the polyvinyl alcohol solution is controlled to be 100:(12-13);
[0022] And / or, the density of the blank obtained after pressing is 3.20g / cm 3 ~3.30g / cm 3 .
[0023] In an optional embodiment, during the sintering of the blank, the sintering temperature is controlled to be 880° C. to 900° C., and the holding time is 180 min to 240 min.
[0024] In an optional embodiment, the sintering temperature rising process includes: firstly, heating from room temperature to 580°C to 620°C at a heating rate of 2°C / min to 3°C / min; then, heating to 780°C to 820°C at a heating rate of 1.5°C / min to 2°C / min, and keeping warm for 60 to 120 minutes; then, heating to 870°C to 890°C at a heating rate of 0.5°C / min to 1.0°C / min, and keeping warm for 180 to 240 minutes;
[0025] And / or, during the heating and sintering process, the atmosphere is air with a flow rate of 1 L / h to 2 L / h.
[0026] In a third aspect, the present invention provides use of the NiCuZn ferrite material of any one of the aforementioned embodiments or the NiCuZn ferrite material prepared by any one of the preparation methods of the aforementioned embodiments in preparing electronic devices.
[0027] The present invention has the following beneficial effects: by 2 O 3 、NiO、ZnO、CuO、Co 2 O 3The comprehensive adjustment of the content takes into account the initial magnetic permeability, quality factor, saturation magnetic flux density and Curie temperature of the material; through the ion replacement of CuO, the iron deficiency, and the Bi in the auxiliary component 2 O 3 As a whole technology, the combination reduces the sintering temperature of the material, accelerates the solid phase reaction and promotes grain growth; 2 O 3 The trace garnet phase generated by Fe increases the cutoff frequency of the material while having little effect on the magnetic permeability; 2 O 3 The small size effect is used for catalysis while no impurities are generated to reduce the magnetic permeability. As a technical invention as a whole, the single technical effect of the present invention cannot form the overall technical effect; the NiCuZn ferrite material provided by the present invention can obtain a uniform material grain structure and grain boundary distribution through a low-temperature sintering process, thereby obtaining a high-reliability low-temperature sintered NiCuZn ferrite material, which can meet the material application in the field of high-reliability electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0029] Figure 1 This is the SEM image of the material prepared in Example 1. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0031] An embodiment of the present invention provides a NiCuZn ferrite material, including a main component and a subsidiary component. The main component has a large content and needs to be pre-burned in advance and then mixed with the subsidiary component during the preparation process; the subsidiary component is introduced as a dopant and has a small content.
[0032] Among them, the main component is the quinary system, including Fe 2 O 3 、NiO、ZnO、CuO、Co 2 O 3 , according to the amount of the main component of the total substance, the content of each component is as follows: Fe2 O 3 47.5~48.7mol%, NiO18.0~18.6mol%, ZnO23.3~24.1mol%, CuO 9.50~9.90mol% and Co 2 O 3 0.48-0.50 mol%. In the NiCuZn ferrite material provided in the embodiment of the present invention, Co 2 O 3 As the main component, it is first mixed with Fe 2 O 3 , NiO, ZnO, CuO are pre-sintered to fully generate CoFe 2 O 4 phase, after secondary crushing, is fully and evenly dispersed throughout the system, giving full play to the CoFe 2 The high frequency performance of the O4 phase helps improve reliability.
[0033] Specifically, based on the amount of the main component, Fe 2 O 3 The content of may be 47.5mol%, 47.8mol%, 48.0mol%, 48.3mol%, 48.5mol%, 48.7mol%, etc.; the content of NiO may be 18.0mol%, 18.1mol%, 18.2mol%, 18.3mol%, 18.4mol%, 18.5mol%, 18.6mol%, etc.; the content of ZnO may be 23.3mol%, 23.4mol%, 23.5mol%, 23.6mol%, 23.7mol%, 23.8mol%, 23.9mol%, 24.0mol%, 24.1mol%, etc.; the content of CuO may be 9.50mol%, 9.60mol%, 9.70mol%, 9.80mol%, 9.90mol%, etc.; the content of Co may be 18.0mol%, 18.1mol%, 18.2mol%, 18.3mol%, 18.4mol%, 18.5mol%, 18.6mol%, etc.; the content of ZnO may be 23.3mol%, 23.4mol%, 23.5mol%, 23.6mol%, 23.7mol%, 23.8mol%, 23.9mol%, 24.0mol%, 24.1mol%, etc. 2 O 3 The content of may be 0.48 mol%, 0.49 mol%, 0.50 mol%, etc.
[0034] Among them, the secondary components include Bi 2 O 3 , Y 2 O 3 、In 2 O 3 , relative to the total weight of the main components, the content of each component is as follows: Bi 2 O 3 1.40~1.60wt%, Y 2 O 3 0.08~0.15wt% and In 2 O3 0.05~0.10wt% Bi in the main component and the auxiliary component 2 O 3 As a whole technology, the combination reduces the sintering temperature of the material, accelerates the solid phase reaction and promotes grain growth; 2 O 3 The trace garnet phase generated by Fe increases the cutoff frequency of the material while having little effect on the magnetic permeability; 2 O 3 The small size effect is used for catalysis without generating impurity phases that reduce the magnetic permeability.
[0035] Specifically, relative to the total weight of the main components, Bi 2 O 3 The content of Y can be 1.40wt%, 1.45wt%, 1.50wt%, 1.55wt%, 1.60wt%, etc.; 2 O 3 The content of may be 0.08wt%, 0.09wt%, 0.10wt%, 0.11wt%, 0.12wt%, 0.13wt%, 0.14wt%, 0.15wt%, etc.; In 2 O 3 The content of may be 0.05wt%, 0.06wt%, 0.07wt%, 0.08wt%, 0.09wt%, 0.10wt% and the like.
[0036] In a preferred embodiment, relative to the total weight of the main component, the auxiliary components include: Bi 2 O 3 1.48~1.52wt%, Y 2 O 3 0.09~0.11wt% and In 2 O 3 0.05-0.07wt%. By further optimizing the composition of the secondary components, the uniformity of the grain structure and grain boundary distribution in the prepared material can be further improved, and the reliability of the NiCuZn ferrite material can be improved.
[0037] The embodiment of the present invention also provides a method for preparing a NiCuZn ferrite material, comprising: preparing the NiCuZn ferrite material that meets the composition requirements by mixing the main components and the auxiliary components provided in the embodiment of the present invention. By improving the composition of the main components and the auxiliary components, the uniformity of the grain structure and grain boundary distribution in the material can be improved, thereby improving the reliability of the material, and significantly reducing the change in inductance during a high temperature load test.
[0038] In some embodiments, the method for preparing the NiCuZn ferrite material provided by the embodiment of the present invention comprises the following steps:
[0039] S1. Preparation of main component pre-sintered material
[0040] First, the ingredients are prepared, mixed, and pre-fired according to the composition of the main component to obtain the main component pre-fired material. The main component is first pre-fired and then mixed with the auxiliary component. Finally, the auxiliary component is controlled to be concentrated at the grain boundary, which is conducive to obtaining a material with a relatively uniform grain structure and grain boundary distribution.
[0041] Specifically, when the main components are mixed, the molar amount of each raw material is calculated according to the amount of the main component total material, and the corresponding mass of Fe 2 O 3 、NiO、ZnO、CuO、Co 2 O 3 .
[0042] In some embodiments, after the ingredients are prepared according to the composition of the main components, the raw materials are mixed by ball milling. Water is added during the ball milling process, and the mass ratio of ball material to water is controlled to be (4.8-5.1): (0.9-1.0): (1.1-1.2). The mixing time is 50 min to 60 min, and the uniformity of the raw material mixing is improved by adjusting the ball milling parameters.
[0043] Specifically, the ball material-water mass ratio can be controlled to be 4.8:0.90:1.10, 4.9:0.95:1.15, 5.0:0.98:1.18, 5.1:1.00:1.20, etc.; the mixing time can be 50 min, 53 min, 55 min, 58 min, 60 min, etc.
[0044] In some embodiments, during the preparation of the main component pre-sintering material, the pre-sintering temperature is controlled to be 810° C. to 830° C., the heat preservation time is 2.0 h to 2.2 h, and then the furnace is cooled. By adjusting the pre-sintering temperature and time, the main component forms a uniform crystal structure.
[0045] Specifically, the pre-firing temperature may be 810° C., 820° C., 830° C., etc., and the holding time may be 2.0 h, 2.1 h, 2.2 h, etc. The pre-firing may be performed in a bell kiln, but is not limited thereto.
[0046] S2. Preparation of activation material
[0047] The main component pre-sintered material and the auxiliary components are mixed and crushed, and then ultrasonically activated to obtain the activated material. The powder uniformity and activity are improved through crushing and ultrasonic activation, and the uniform material grain structure and grain boundary distribution are further obtained by combining the sintering process, thereby obtaining a high-reliability low-temperature sintered NiCuZn ferrite material, which can meet the material application in the field of high-reliability electronic devices.
[0048] Specifically, according to the mass fraction of each component in the auxiliary component to the total mass of the main component, calculate the actual added mass of each component, weigh the corresponding mass of Bi 2 O 3 , Y 2 O 3 、In 2 O 3 .
[0049] In some embodiments, the main component pre-sintered material and the auxiliary components are pulverized by wet pulverization, the pulverization time is 120min to 130min, and the median particle size of the slurry after pulverization is 0.6μm-0.80μm. The wet pulverization method can improve the uniformity of the particles after pulverization.
[0050] Specifically, a vertical sand mill can be used for wet grinding, and the grinding time can be 120 min, 125 min, 130 min, etc.; the median particle size of the slurry after grinding can be controlled to be about 0.95 μm-1.10 μm, etc.
[0051] In some embodiments, the ultrasonic activation treatment includes: subjecting the crushed slurry to ultrasonic crushing, so that the D10, D50, and D90 particle sizes of the particles in the slurry are all <1.0 μm, and the slurry temperature is controlled at 80° C.-85° C. Through further ultrasonic crushing, the particle size is further reduced, and the particle size is more uniform, and the microparticles are more active after obtaining heating energy, and the system is more evenly dispersed.
[0052] Specifically, ultrasonic crushing can be carried out using a commercially available ultrasonic crusher. The temperature of the slurry can be controlled at 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, etc. during the crushing process. By adjusting the crushing time, the D10, D50, and D90 particle sizes of the particles in the slurry after ultrasonic crushing can all be <1.0μm, etc.
[0053] S3, granulation, pressing
[0054] The activated material obtained in step S2 is granulated and pressed to obtain a blank. A uniform granular material is obtained by granulation, and a blank having a pressing density that meets the requirements is obtained by pressing.
[0055] In some embodiments, the granulation process includes: mixing the activated material with the polyvinyl alcohol solution, performing high-speed centrifugal granulation, and obtaining uniform granular material. The mass fraction of the polyvinyl alcohol solution is 7%-9% (such as 7%, 8%, 9%, etc., and the solvent can be water), and the mass ratio of the activated material to the polyvinyl alcohol solution is controlled to be 100: (12-13), such as 100: 12.0, 100: 12.5, 100: 13.0, etc. That is, the amount of polyvinyl alcohol solution added is 12%-13% of the solid weight of the slurry.
[0056] In some embodiments, the pressing can be processed by a powder forming machine, and the pressing density of the blank obtained after pressing is 3.20 g / cm 3 ~3.30g / cm 3 , such as 3.20g / cm 3 , 3.25g / cm 3 3.30g / cm 3 wait.
[0057] S4, Sintering
[0058] The blank obtained in step S3 is sintered to prepare a nickel-zinc ferrite magnetic ring sample.
[0059] In some embodiments, during the sintering process of the blank, the sintering temperature is controlled to be 880° C. to 900° C., the holding time is 170 min to 200 min, the sintering atmosphere can be air, and after the sintering is completed, the blank is cooled to room temperature with the furnace.
[0060] Specifically, the sintering temperature can be 880°C, 885°C, 890°C, 895°C, 900°C, etc.; the holding time can be 170 min, 180 min, 190 min, 200 min, etc.
[0061] In a preferred embodiment, the sintering temperature rise process includes: firstly, the temperature is raised from room temperature to 580℃~620℃ at a heating rate of 2℃ / min~3℃ / min; then, the temperature is further raised to 780℃~820℃ at a heating rate of 1.5℃ / min~2℃ / min, and the temperature is kept for 60~120min; then, the temperature is further raised to 870℃~890℃ at a heating rate of 0.5℃ / min~1.0℃ / min, and the temperature is kept for 180~240min; during the heating and sintering process, the atmosphere is air, and the flow rate is 1L / h~2L / h. By further controlling the process of programmed heating, the uniformity of the grain structure and grain boundary distribution in the product obtained after sintering is improved.
[0062] Specifically, the heating stage is divided into three sections. The first heating process is from room temperature to 580°C-620°C (such as 580°C, 600°C, 620°C, etc.), and the heating rate can be 2.0°C / min, 2.5°C / min, 3.0°C / min, etc.; the second heating process is from 580°C-620°C to 780°C-820°C (such as 780°C, 800°C, 820°C, etc.), and the heating rate can be 1.5°C / min, 1.8°C / min, 2.0°C / min, etc., and the heating rate can be 1.5°C / min, 1.8°C / min, 2.0°C / min, etc. After reaching 780°C ~ 820°C, the holding time can be 60min, 80min, 100min, 120min, etc.; the third heating process is from 780°C ~ 820°C to 870°C ~ 890°C (such as 870°C, 880°C, 890°C, etc.), the heating rate can be 0.5°C / min, 0.8°C / min, 1.0°C / min, etc., and the holding time after heating to 870°C ~ 890°C can be 180min, 200min, 220min, 240min, etc.
[0063] The NiCuZn ferrite material provided by the embodiment of the present invention can be further prepared into electronic devices, which can further improve the reliability of the electronic devices.
[0064] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0065] Example 1
[0066] This embodiment provides a NiCuZn ferrite material, including a main component and a secondary component. The main component includes: Fe 2 O 3 47.6mol%, NiO 18.5mol%, ZnO 23.8mol%, CuO 9.60mol%, Co 2 O 3 0.50mol%; relative to the total weight of the main component, the auxiliary components include: Bi 2 O 3 1.50wt%, Y 2 O 3 0.10wt% and In 2 O 3 0.06wt%.
[0067] This embodiment also provides a method for preparing a NiCuZn ferrite material, the steps are as follows:
[0068] (1) The ingredients are mixed in a mixing device according to the proportion of the main components, the ball material water ratio is 5:1:1.2, and the mixing time is 60 minutes. The mixed materials are pre-fired in a bell kiln, the pre-fired temperature is controlled at 820°C, and the temperature is kept for 2 hours and then cooled with the furnace to obtain the main component pre-fired material.
[0069] (2) After adding the auxiliary components to the main component pre-calcined material obtained in step (1), the material is wet-milled using a vertical sand mill for 120 min. The median particle size of the slurry after milling is controlled at 1.05 μm. The obtained slurry is ultrasonically milled. The particle sizes of slurry D10, D50, and D90 are all controlled at about 0.4 μm. The slurry temperature is controlled at 83° C. to obtain an activated material.
[0070] (3) Add 12.5% polyvinyl alcohol solution (mass fraction 8%) equivalent to the solid weight of the slurry to the activated material obtained in step (2), and use high-speed centrifugal granulation (speed 10000rpm) to obtain uniform granular material. The obtained granular material is pressed into a blank using a powder molding machine, and the pressing density of the blank is controlled at 3.25g / cm 3 .
[0071] (4) The blank obtained in step (3) is sintered in a resistance furnace, and the sintering temperature is controlled at 890°C, and the temperature is kept for 180 minutes. The sintering atmosphere is air, and the flow rate is 1.5L / h. After sintering, it is cooled to room temperature with the furnace. The sintering heating process is: first from room temperature to 600°C at 3°C / min; then from 600°C to 800°C at 1.5°C / min, and kept for 100 minutes; then from 800°C to 890°C at 1.0°C / min, and kept for 240 minutes. The atmosphere is air. The nickel-zinc ferrite magnetic ring sample size obtained by the above process is: outer diameter 12.7mm×inner diameter 7.9mm×thickness 6.5mm.
[0072] Figure 1 This is the SEM image of the ferrite material prepared in Example 1. It can be seen that the size of the grains in the material is relatively uniform, which greatly reduces the stress inside the material and makes the internal structure more stable, so that the material performance obtains higher stability.
[0073] The sintered magnetic rings were tested and evaluated respectively: the real and imaginary parts of the complex permeability of the samples at 1MHz and 10MHz were measured using the E4991B tester; the Curie temperature Tc of the samples was tested using the HP4284A in conjunction with the MC-711 small ultra-low temperature test chamber and the PHH-101 high temperature test chamber; the saturation magnetic flux density Bs of the samples was tested using the SY-8218 BH analyzer;
[0074] The technical effects of Example 1 are as follows:
[0075] Real part of complex permeability μ′: 108~110, (f=1~10MHz, 100mV, 25℃);
[0076] Complex permeability imaginary part μ″: 0.55, (f = 1MHz, 100mV, 25℃); 0.92, (f = 10MHz, 100mV, 25℃);
[0077] Quality factor Q: ≥110 (f = 1 ~ 10MHz, 100mV, 25℃);
[0078] Saturation flux density Bs: 409mT, (f = 1kHz, Hm = 4000A / m, 25℃);
[0079] Curie temperature Tc:>245℃,(f=10kHz,B<0.25mT);
[0080] ① High temperature 125℃, relative humidity 60%, stable for 96h, the change rate of magnetic ring inductance is 0.98%; ② Low temperature -40℃, relative humidity 60%, stable for 96h, the change rate of magnetic ring inductance is 1.06%; ③ Temperature 60℃, relative humidity 95%, stable for 504h, the change rate of magnetic ring inductance is 1.54%; ④ Temperature -40℃~120℃, relative humidity 60%, cycle 100 times, keep warm at extreme temperature for 30 minutes, temperature conversion time ≤5 minutes, the change rate of magnetic ring inductance before and after is 1.60%.
[0081] The preparation methods in the following examples and comparative examples are prepared according to the main components and auxiliary components of the NiCuZn ferrite materials provided by each, and the specific preparation process refers to Example 1.
[0082] Example 2
[0083] The only difference from Example 1 is that the composition of the auxiliary components is different. Based on the total weight of the main components, the auxiliary components include: Bi 2 O 3 1.40wt%, Y 2 O 3 0.10wt% and In 2 O 3 0.05wt%.
[0084] Example 3
[0085] The only difference from Example 1 is that the composition of the auxiliary components is different. Based on the total weight of the main components, the auxiliary components include: Bi 2 O 3 1.60wt%, Y 2 O 3 0.15wt% and In 2 O 30.10wt%.
[0086] Comparative Example 1
[0087] The only difference from Example 1 is that the dosage of each component remains unchanged, and the Co 2 O 3 It is added together with the auxiliary ingredients in step (2) during the preparation process.
[0088] Comparative Example 2
[0089] The only difference from Example 1 is that the secondary components do not contain Y 2 O 3 .
[0090] Comparative Example 3
[0091] The only difference from Example 1 is that the secondary component does not contain In 2 O 3 .
[0092] The proportions of the raw materials in the embodiments and comparative examples are shown in Table 1.
[0093] Table 1 Proportions of raw materials in Examples and Comparative Examples
[0094]
[0095]
[0096] The properties of the ferrite materials prepared in the examples and comparative examples are shown in Table 2:
[0097] Table 2 Properties of ferrite materials prepared in Examples and Comparative Examples
[0098]
[0099] Note: "+" means the upper specification is exceeded, "*" means the lower specification is exceeded
[0100] It can be seen that the NiCuZn ferrite material prepared in the embodiment takes into account the requirements of multiple technical indicators such as high magnetic permeability, high Bs, high quality factor, etc., and its reliability is significantly higher than that of the comparative example.
[0101] In summary, the preparation process of the NiCuZn ferrite material provided by the embodiment of the present invention is simple to operate and low in cost, and well takes into account the requirements of multiple technical indicators such as low temperature sintering, high magnetic permeability, high Bs, high quality factor, etc., and is particularly characterized by high reliability, which is very suitable for the production needs of high-reliability laminated chip magnetic devices and modules. Specifically, the performance parameters of the NiCuZn ferrite material provided by the embodiment of the present invention are as follows:
[0102] (1) Real part of complex permeability μ′: 100-120, (f=1-10MHz, 100mV, 25℃);
[0103] Complex permeability imaginary part μ″: ≤0.6, (f=1MHz, 100mV, 25℃); ≤1.0, (f=10MHz, 100mV, 25℃);
[0104] (2) Quality factor Q: ≥100 (f = 1 ~ 10MHz, 100mV, 25℃);
[0105] (3) Saturation magnetic flux density Bs: ≥405mT, (f = 1kHz, Hm = 4000A / m, 25℃);
[0106] (4) Curie temperature Tc: ≥245°C, (f=10kHz, B<0.25mT);
[0107] (5) At high temperature of 125°C and relative humidity of 60%, the change rate of the magnetic ring inductance is less than 2.0% after 96 hours of stability; at low temperature of -40°C and relative humidity of 60%, the change rate of the magnetic ring inductance is less than 2.0% after 96 hours of stability; at temperature of 60°C and relative humidity of 95%, the change rate of the magnetic ring inductance is less than 2.0% after 504 hours of stability; at temperature of -40°C to 120°C and relative humidity of 60%, the cycle is repeated 100 times, the temperature is kept at the extreme temperature for 30 minutes, the temperature conversion time is ≤5 minutes, and the change rate of the magnetic ring inductance before and after is less than 2.0%.
[0108] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A NiCuZn ferrite material, characterized in that: Includes main components and secondary components; Wherein, according to the amount of the total substance of the main component, the main component includes: Fe2O3 47.5-48.7mol%, NiO 18.0-18.6mol%, ZnO 23.3-24.1mol%, CuO 9.50-9.90mol% and Co2O3 0.48-0.50mol%; Relative to the total weight of the main component, the auxiliary components include: Bi2O3 1.40-1.60wt%, Y2O3 0.08-0.15wt% and In2O3 0.05-0.10wt%.
2. The NiCuZn ferrite material according to claim 1, characterized in that: Relative to the total weight of the main component, the auxiliary components include: Bi2O3 1.48-1.52wt%, Y2O3 0.09-0.11wt% and In2O3 0.05-0.07wt%.
3. A method for preparing the NiCuZn ferrite material according to claim 1 or 2, characterized in that: include: The ingredients are prepared according to the composition of the main component and the auxiliary component to prepare a NiCuZn ferrite material that meets the component composition requirements.
4. The preparation method according to claim 3, characterized in that: include: Firstly, the ingredients are batched, mixed and pre-fired according to the composition of the main component to obtain a main component pre-fired material; The main component pre-sintered material and the auxiliary component are mixed and crushed, and then ultrasonically activated to obtain an activated material; Granulating and pressing the activated material to obtain a blank; The green body is sintered.
5. The preparation method according to claim 4, characterized in that: After the ingredients are prepared according to the composition of the main component, the raw materials are mixed by ball milling, and the mass ratio of ball material to water is controlled to be (4.8-5.1): (0.9-1.0): (1.1-1.2), and the mixing time is 50min-60min; And / or, during the preparation of the main component pre-burned material, the pre-burning temperature is controlled to be 810° C. to 830° C., and the insulation time is 2.0 h to 2.2 h.
6. The preparation method according to claim 4, characterized in that: The main component pre-sintered material and the auxiliary component are pulverized by wet pulverization, the pulverization time is 120min to 130min, and the median particle size of the slurry after pulverization is 0.95μm to 1.10μm; And / or, the ultrasonic activation treatment includes: subjecting the pulverized slurry to ultrasonic pulverization, so that the D10, D50 and D90 particle sizes of the particles in the slurry are all less than 1.0 μm, and controlling the slurry temperature to 80° C.-85° C. during the pulverization process.
7. The preparation method according to claim 4, characterized in that: The granulation process comprises: mixing the activated material with a polyvinyl alcohol solution and centrifugally granulating; the mass fraction of the polyvinyl alcohol solution is 7%-9%, and the mass ratio of the solid mass in the activated material to the polyvinyl alcohol solution is controlled to be 100:(12-13); And / or, the density of the blank obtained after pressing is 3.20 g / cm 3 ~3.30g / cm 3 .
8. The preparation method according to claim 4, characterized in that: During the sintering of the blank, the sintering temperature is controlled to be 880° C. to 900° C., and the heat preservation time is 180 min to 240 min.
9. The preparation method according to claim 8, characterized in that: The sintering temperature rising process includes: firstly, the temperature is raised from room temperature to 580°C to 620°C at a heating rate of 2°C / min to 3°C / min; then, the temperature is further raised to 780°C to 820°C at a heating rate of 1.5°C / min to 2°C / min, and the temperature is kept for 60 to 120 minutes; then, the temperature is further raised to 870°C to 890°C at a heating rate of 0.5°C / min to 1.0°C / min, and the temperature is kept for 180 to 240 minutes; And / or, during the heating and sintering process, the atmosphere is air with a flow rate of 1 L / h to 2 L / h.
10. Use of the NiCuZn ferrite material according to any one of claims 1 to 2 or the NiCuZn ferrite material prepared by the preparation method according to any one of claims 3 to 9 in preparing electronic devices.
Citation Information
Cited By
Low-temperature sintered NiCuZn ferrite material with high initial permeability and low power loss and preparation method thereof
CN122277241A